Empowering Communities Through Capacity Building Dental And Oral Health Screening And Counseling In Kedungwinong - Yuanita Anwaristi, Aprilia; Cahyani (Journal of Community Capacity Empowerment, 2024)
The main issue for the elderly is the loss and damage of many teeth, leading to difficulties in chewing food. The most common cause of tooth loss is poor oral health, particularly dental caries and periodontitis. Elderly individuals often neglect oral hygiene and frequently complain of dental issues such as loose teeth, cavities, or swollen gums. The purpose of empowering communities through capacity building was to increase awareness of the importance of maintaining overall health, dental and oral health, and to assess the level of knowledge and the status of dental and oral health among the residents of Kedung Winong. The proposed solution to the problem is to increase residents' awareness of maintaining dental and oral health, enhance their knowledge of proper tooth brushing techniques, promote the habit of brushing teeth at appropriate times, and raise awareness about the importance of regular health check-ups as a preventive measure against chronic diseases. Methods of oral health counseling and examinations was chosen to solve the problems. The counseling and examination activities for the community in the Muhammadiyah and Aisyiyah branches in Kedungwinong, Nguter, Sukoharjo, were successfully implemented, with enthusiastic and cooperative participation. The activities effectively raised awareness about the importance of dental and oral health.